2011
DOI: 10.1007/s00262-011-1152-x
|View full text |Cite
|
Sign up to set email alerts
|

Potent antitumor effects of combination therapy with IFNs and monocytes in mouse models of established human ovarian and melanoma tumors

Abstract: Interferon-activated monocytes are known to exert cytocidal activity against tumor cells in vitro. Here, we have examined whether a combination of IFN-α2a and IFN-γ and human monocytes mediate significant antitumor effects against human ovarian and melanoma tumor xenografts in mouse models. OVCAR-3 tumors were treated i.t. with monocytes alone, IFN-α2a and IFN-γ alone or combination of all three on day 0, 15 or 30 post-tumor implantation. Mice receiving combination therapy beginning day 15 showed significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…monocytes, macrophages, T cells and NK cells (33). An animal study showed increased regression of tumor nodules and survival of animals after treatment with IFN-c (34).…”
Section: Obesitymentioning
confidence: 99%
“…monocytes, macrophages, T cells and NK cells (33). An animal study showed increased regression of tumor nodules and survival of animals after treatment with IFN-c (34).…”
Section: Obesitymentioning
confidence: 99%
“…We evaluated granulocytes (Gr1 + CD11b - ), MDSCs (Gr1 + CD11b + ), and tumor-associated macrophages (TAMs, Gr1 - CD11b + ). Markers utilized to identify activation were FasL [1], CXCL9 [2], CD31 [3], and CD105 [4]. …”
Section: Methodsmentioning
confidence: 99%
“…We have expanded this observation to show that IFNs are potent killers of ovarian cancer cells lines, and there is synergism with the IFNs and the current standard of care of carboplatin and paclitaxel[54]. IFN-α can also induce tumor cell apoptosis by stimulating the tumor cells to produce the cell death ligand TRAIL, which through an autocrine feedback loop, kills the tumor cells expressing the receptors for TRAIL (DR4/DR5)[55]. TRAIL signaling results in a Caspase 8 mediated cleavage of BID to tBID, followed by Bak dimerization, loss of mitochondrial membrane potential and release of apoptosis inducing factor which results in cell death in ovarian cancer cells (OVCAR3)[55].…”
Section: Interferons and The Treatment Of Cancermentioning
confidence: 99%
“…In 2007 we showed that while IFNs were capable of inducing cytotoxicity in a number of cancer cell lines, the addition of monocytes to the culture significantly increased the cytotoxicity[53]. Using a intratumoral injection, mouse model with an human ovarian cancer cell line we showed that while there was no significant reduction in tumor size with IFNs or monocytes alone, there was significant decrease in tumor volume and complete response in some animals that received injection of IFNs and monocytes at the time of tumor initiating[55]. Importantly administration of IFNs and monocytes 15 days after the injection of tumor cells exhibited a similar response to Day 0 in both tumor volume and complete response.…”
Section: Monocytes and Macrophagesmentioning
confidence: 99%